2000
DOI: 10.1086/308515
|View full text |Cite
|
Sign up to set email alerts
|

Flickering in FU Orionis

Abstract: We analyze new and published optical photometric data of FU Orionis, an eruptive pre-main sequence star. The outburst consists of a 5.5 mag rise at B with an e-folding timescale of roughly 50 days. The rates of decline at B and V are identical, 0.015 +- 0.001 mag per yr. Random fluctuations superimposed on this decline have an amplitude of 0.035 +- 0.005 mag at V and occur on timescales of 1 day or less. Correlations between V and the color indices U-B, B-V, and V-R indicate that the variable source has the op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 53 publications
(53 reference statements)
7
66
2
Order By: Relevance
“…For FU Ori, Kenyon et al (2000) find a non-periodic variability of 33 mmag at the V band, after removal of a 17-day period with an amplitude of 9 mmag. They use a lower sampling rate (∼few per day) but consider a multiband (UBVR) data set, and conclude that 35 mmag variations (correlated over multiple color bands) must occur on timescales <1 day, comparable to the dynamic timescale of the inner disk.…”
Section: Comparison To Other Studies Of Young Stellar Objectsmentioning
confidence: 87%
See 1 more Smart Citation
“…For FU Ori, Kenyon et al (2000) find a non-periodic variability of 33 mmag at the V band, after removal of a 17-day period with an amplitude of 9 mmag. They use a lower sampling rate (∼few per day) but consider a multiband (UBVR) data set, and conclude that 35 mmag variations (correlated over multiple color bands) must occur on timescales <1 day, comparable to the dynamic timescale of the inner disk.…”
Section: Comparison To Other Studies Of Young Stellar Objectsmentioning
confidence: 87%
“…Observations of T Tauri stars (Stassun et al 1999;Rucinski et al 2008) and Herbig Ae/Be stars (Rucinski et al 2010) find indications of the stellar rotation and asymmetry due to a collection of hot or cool spots (Herbst et al 2007), but only sparse evidence of direct accretion processes. Additionally, pulsations and random reddening events in young stellar objects were considered in Kenyon et al (2000) but found to be unlikely as the cause of observed ∼0.03 mag variability. Finally, some evidence for hour-timescale variability has been found in short-lived excited modes in shorter-duration outbursts, EXors (Bastien et al 2011), likely more evolved sources than FUors.…”
Section: Introductionmentioning
confidence: 99%
“…FU Ori is the prototype of the FU Orionis phenomenon. While the SIMBAD database lists a spectral type of G3Iavar, Kenyon et al (2000) changed it to G0II. In contrast to Hanner et al (1998), who measured an increasing MIR flux shortward of 10 μm, the spectra of Schegerer et al (2006) and Quanz et al (2006) agree very well with ours, indicating that this object was not variable in the MIR between Dec. 2002 and Jan. 2006 (or at least that any period of variability was not observed).…”
Section: Appendix A: Comments On Individual Sourcesmentioning
confidence: 99%
“…The low mass pre-main sequence star FU Orionis (hereafter, FU Ori) brightened by ∆B = 6 mag in 1936 (Herbig 1977), and subsequently has declined slowly (∼ 0.013 mag/yr; Kenyon et al 2000) to the present day. This outburst established a prototype class of variable star (FU Orionis objects, or "FUors"; Hartmann & Kenyon 1996;Hartmann 1998) that ∼10 other stars have since matched.…”
Section: Introductionmentioning
confidence: 99%